A single blood luteinizing hormone level of triptorelin stimulation test can diagnose hypothalamic-pituitary-gonadal axis activation in girls with high body mass index - Zeng, Beilei; Huang, Yinyin; Zhou, Yuan; Li, Ye; Huang, Panwang; Xu, Zhuangjian; Ma, Yaping (Frontiers in Pediatrics, 2025)
BackgroundBody mass index (BMI) may influence peak luteinizing hormone (PLH) levels during gonadotropin releasing hormone (GnRH) or GnRH analogues stimulation testing. BMI effects should be considered when interpreting test results for pubertal disorders in girls with overweight/obesity, but few studies have excluded it.MethodsThis was a hospital data-based retrospective study. Girls with puberty disorders who had been followed up for six months to two years were enrolled in the study. They were divided into the overweight/obesity group and the normal BMI group and all underwent triptorelin stimulation test. Blood samples were collected at 0 min before and 20, 40, and 60 min after the test. Luteinizing hormone (LH) and follicle-stimulating hormone (FSH) serum concentrations were quantified by immunochemiluminometric assay.ResultsA total of 422 girls who underwent 454 triptorelin stimulation tests were included in this study. Among 148 tests performed on 142 overweight/obesity girls, 110 tests were hypothalamic-pituitary-gonadal axis (HPGA) activated and 38 tests were HPGA non-activated. Among 306 tests performed on 284 girls with normal BMI, 214 tests were HPGA activated and 92 tests were non-activated. LH, FSH, and estradiol levels in girls whose HPGA activated were significantly higher than those non-activated. The area under the curves of LH20 min, LH40 min, LH60 min and PLH after triptorelin stimulation tests in girls with overweight/obesity for diagnosing HPGA activation were 0.996, 0.980, 0.990 and 0.994, respectively. There was no statistical significance in the area under the curves between LH20 min, LH40 min, LH60 min and PLH. When LH20 min, LH40 min, LH60 min and PLH were ≥3.26 IU/L, ≥4.09 IU/L, ≥4.27 IU/L and ≥4.51 IU/L, the sensitivity for diagnosing HPGA activation in girls with overweight/obesity were 99.03%, 95.45%, 98.18% and 97.27%, and the corresponding specificity were 94.59%, 97.37%, 100.00%, and 100.00%, respectively. The cut-off value of serum LH60 min after the triptorelin stimulation test for diagnosing HPGA activation in precocious pubertal girls with overweight/obesity was 4.45 IU/L, and in pubertal girls with overweight/obesity was 4.20 IU/L.ConclusionsLH measurements obtained at 20, 40, or 60 min post-triptorelin stimulation can diagnose HPGA activation in girls with high BMI.